Reclaiming accountability : improving writing programs through accreditation and large-scale assessments - Sharer, Wendy B.; Morse, Tracy Ann; Eble, Michelle F., 1974-; Banks, Will (Utah State University Press, 2016)
"Reclaiming Accountability brings together a series of critical case studies of writing programs that have planned, implemented, and/or assessed the impact of large-scale accreditation-supported initiatives and reimagines accreditation as a way to leverage institutional or program change and addresses assessment requirements beyond those in writing programs"--